Research productivity of sociology PhD candidates at interdisciplinary schools of social science at elite Australian universities, 2013–17: A gender perspective. (September 2021) - Rajčan, Adam; Burns, Edgar A.
Gender data are presented from a study into sociology PhD completions and student research outputs during enrolment at Australian 'Group of Eight' interdisciplinary schools of social science. Findings confirm views and impressions offered by Australian sociology academic leaders. The present data contributes to this wider discussion by describing patterns in the contemporary cohort of sociology PhD students. First, we document a stable gender composition of the discipline in Australia reflective of the literature across several decades rather than a recent feminisation process. Second, we report for this cohort of contemporary PhD sociology completions in Australia women and men publish at similar rates during candidacy. Third, there is no significant gendered difference between students at any level of research output production. Fourth, methodological approaches used by sociology doctoral students confirm the epistemological domination of qualitative analysis in this current cohort of sociology PhD theses.